Incidence of and risk factors for severe maternal complications associated with hypertensive disorders after 36 weeks' gestation in uncomplicated twin pregnancies: A prospective cohort study. Issue 7 (19th April 2018) - Yamamoto, Ryo; Ishii, Keisuke; Muto, Haruka; Ota, Shiyo; Kawaguchi, Haruna; Hayashi, Shusaku; Mitsuda, Nobuaki
Abstract: Aim: To elucidate the incidence of and risk factors for severe hypertensive disorders (HD) and related maternal complications in uncomplicated twin pregnancies that reached 36 weeks' gestation. Methods: We conducted a prospective cohort study of twin pregnancies delivered after 36 weeks' gestation. Cases of twin–twin transfusion syndrome, twin anemia–polycythemia sequence, malformed fetuses, monoamniotic twins, selective reduction, fetal therapy and HD or fetal death before 35 weeks' gestation were excluded. The study's primary outcome was the incidence of severe maternal complications, including severe HD, eclampsia, placental abruption, HELLP (hemolysis, elevated liver enzyme and low platelet) syndrome, pulmonary edema and cerebrovascular disease. Perinatal factors associated with the primary outcome were identified using a multivariate logistic regression model. Results: In 330 enrolled women, the number of cases with the primary outcome was 28 (8.5%; 95% confidence interval 5.9–12.0), including 25 cases of severe HD and each one case of placental abruption, HELLP syndrome and eclampsia. The rate of severe maternal complications significantly increased with gestational age, demonstrating 1.2% at 36 weeks, 3.9% at 37 weeks and 6.4% at 38 weeks. Only gestational proteinuria was identified as the independent risk factor for severe maternal complications (adjusted odds ratio 17.1 [95% confidence interval 6.71–45.4]). Conclusion: Severe maternal HD and related complications increased from late preterm to early term; particularly, patients with gestational proteinuria were at high risk.